2018
DOI: 10.1093/ofid/ofy201
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Waist Circumference in HIV-Infected Individuals Initiating a Raltegravir or Protease Inhibitor Regimen: Effects of Sex and Race

Abstract: Background This study investigates the association of clinical and demographic predictors with abdominal fat gain, measured using waist circumference (WC) and self-reported abdominal size. Methods We analyzed data from ACTG A5257, a clinical trial that randomized treatment-naïve HIV-infected participants to 1 of 3 antiretroviral regimens: raltegravir (RAL) or the protease inhibitors (PIs) atazanavir/ritonavir (ATV/r) or darun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 43 publications
3
44
2
Order By: Relevance
“…However, the similarities in weight change observed across core groups do raise questions as to the role of concurrent switches to TAF in weight changes reported with switches to InSTI. Finally, the estimated weight loss over time on TDF observed in OPERA among PLWH who maintained raltegravir did not align with the literature suggesting weight gain with raltegravir even without TAF use [25,26,[35][36][37]. However, this may reflect an age-related decline in weight, as raltegravir was prescribed to an older population.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the similarities in weight change observed across core groups do raise questions as to the role of concurrent switches to TAF in weight changes reported with switches to InSTI. Finally, the estimated weight loss over time on TDF observed in OPERA among PLWH who maintained raltegravir did not align with the literature suggesting weight gain with raltegravir even without TAF use [25,26,[35][36][37]. However, this may reflect an age-related decline in weight, as raltegravir was prescribed to an older population.…”
Section: Discussionmentioning
confidence: 69%
“…The marked increase in weight immediately following TAF initiation observed in OPERA was in line with results in ART-na€ ıve PLWH in clinical trials [10,12] and in the CFAR Network of Integrated Clinical Systems (CNICS) cohort [31]. While multiple studies have shown greater weight gains with InSTI-based regimen overall [11,12,[17][18][19][20][21][22][23][24][25][26] or specifically with dolutegravir, bictegravir or raltegravir [10][11][12]18,19,22,[25][26][27][28][29][30][31][35][36][37] compared to other regimens, most did not account for the role of TAF. In OPERA, the estimated rates of weight gain were numerically slightly higher in the first nine months of TAF when maintaining an InSTI, elvitegravir/cobicistat or dolutegravir, and when switching to bictegravir or dolutegravir, although differences between groups were not tested directly, and confidence intervals overlapped.…”
Section: Discussionmentioning
confidence: 99%
“…In Cohort 2, women were more than twice as likely as men to have multimorbidity. Other studies have documented a higher prevalence of obesity among women, particularly in those on ART regimens containing tenofovir alafenamide and integrase strand inhibitors, especially dolutegravir and bictegravir [ 30 , 31 ]. We did not collect data on the specifics of the ART regimen for the participants; however, it is possible that participants in Cohort 2 were prescribed regimens associated with increases in weight that disproportionately affect women.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lower rate of multimorbidity for those with private insurance, which was likely related to better access to non-HIV preventative care, the RWHAP should consider a targeted investment to deliver more preventative care in RWHAP clinics with the goal of reducing multimorbidity prevalence in PWH. This is especially important given the growing evidence about the impact of HIV and ART on cardiovascular risk and weight gain [ 4 , 30 , 31 ]. The higher rate of multimorbidity in women in the aging PWH population should be investigated further, and RWHAP Part D should consider expanding their support for this population’s non-HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…Specific ART regimens or drug classes have also been implicated in weight gain, with integrase strand transfer inhibitors (INSTIs) cited in 2 randomized studies [5] and several retrospective cohort studies [6]. Highly active antiretroviral therapy (HAART)-induced lipoatrophy, currently the most common form of lipoatrophy worldwide, is associated with hypoleptinemia, insulin resistance, and elevated triglycerides in the context of the HAART-induced metabolic syndrome (HAART-MS) [7].…”
Section: Introductionmentioning
confidence: 99%